FACTORS INFLUENCING WORKING MOTIVATION OF AGRICULTURAL EXTENSION AGENTS IN CENTRAL JAVA PROVINCE - Warsana, Warsana; Sumekar, Wulan; Luqman, Yanuar (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Productivity of rice in Pekalongan and Jepara regencies is the lowest in the Pantura region of Central Java province. One of the problems is that the number of extension workers is still insufficient and is not balanced with the area of agricultural areas in the district. The existence of agricultural instructors has a positive impact on farmer behavior, including knowledge, attitudes and skills. The more advanced farmers' behavior will have the impact of increasing the productivity of their farming This indicates that the program of one Agricultural Extension Agent for one village has not been fulfilled. This research was conducted to analyze education, experience, and workload toward work motivation in the field. Survey approach was used in this research. Sampling was done using a proportionate random sampling as a sampling technique for selecting respondents with total 122 agricultural extension agents in Pekalongan and Jepara regencies. Data sources using primary data and secondary data Multiple regression was used for data analysis. The results of the study show that education, work experience and workload had influence both simultaneously and partially toward work motivation of extension workers in Pekalongan City and Jepara. Good education and better experience with appropriate workload can increase motivation. It need approach to maintain a moderate workload to improve work motivation. Agricultural Extension Workers with high work motivation provide the best performance during extension activities. The conclusion of this research is that all hypotheses in this research are accepted and have a positive and significant influence. Extension workers are expected to be able to maintain their work so that the work motivation of Agricultural Extension workers is maintained.